2023
DOI: 10.1017/s1368980023002379
|View full text |Cite
|
Sign up to set email alerts
|

Social and ecological disparities in anaemia among adolescent girls 15–19 years old in Nepal

Anjana Rai,
Mei Ting Chan,
Smita Nambiar

Abstract: Objective Adolescent girls are at risk of anaemia due to the increased nutrient demands because of growth, menstrual blood loss and possible pregnancies. Sociocultural and household conditions influence their risk. We aimed to identify the sociocultural and economic factors of anaemia in adolescent girls in Nepal. Design The Nepal Demographic and Health Surveys (NDHS) conducted in 2006, 2011, and 2016 were pooled for secondary analysis. We used data on haemoglobin measurements for anaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Several studies have found inverse associations of serum Hb levels with antirheumatic medication, PIR, and CRP. [ 34 36 ] To eliminate the possibility of antirheumatic medication, PIR, and CRP affecting our results, we adjusted for them in the sensitivity analysis. We found that there was still an association between the DII and the risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found inverse associations of serum Hb levels with antirheumatic medication, PIR, and CRP. [ 34 36 ] To eliminate the possibility of antirheumatic medication, PIR, and CRP affecting our results, we adjusted for them in the sensitivity analysis. We found that there was still an association between the DII and the risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the sensitivity analysis, we adjusted for antirheumatic medication, family poverty income ratio (PIR), and C-reactive protein (CRP) as covariates in weighted multivariate logistic regressions to minimize their potential impact on the association between the DII and anemia in RA patients. [ 34 36 ] We carried out stepwise regression and the nomogram model to further identify the association between anemia and DII. The receiver operating characteristic curve was performed to determine the discriminatory ability of the nomogram model in identifying anemic risk.…”
Section: Methodsmentioning
confidence: 99%